2020
DOI: 10.21203/rs.3.rs-29536/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Helicobacter pylori infection and its correlates among the patients of peptic perforation and gastric carcinoma

Abstract: Background: Presence of H. pylori infection was found associated with peptic perforation and gastric carcinoma. Present study tried to estimate the prevalence of H. pylori infection in those patients and to find out the correlates of H. pylori infection.Methods: After matching the inclusion and exclusion criteria, all cases of diagnosed peptic perforation and gastric carcinoma were taken for this prospective, single center, observational study.Results: Among the study population, gastric carcinoma was found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The present study found that around three-fourths of the patients were Hindus and 22.5% were Muslims and most of them were married (85%), which corresponds to the study done by Saha et al ,[ 11 ] which also reported most of the patients suffering from perforated ulcer were Hindus and married persons were the commonest. The beneficiaries of the studied hospital are mostly Hindus, and this has been reflected in the findings of the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study found that around three-fourths of the patients were Hindus and 22.5% were Muslims and most of them were married (85%), which corresponds to the study done by Saha et al ,[ 11 ] which also reported most of the patients suffering from perforated ulcer were Hindus and married persons were the commonest. The beneficiaries of the studied hospital are mostly Hindus, and this has been reflected in the findings of the present study.…”
Section: Discussionsupporting
confidence: 90%
“…In a study by Saha et al [ 11 ] observed that RUT, an indicator of H. pylori infection, was positive in 82% patients of with peptic perforation. The present study has reported almost a similar result (80%).…”
Section: Discussionmentioning
confidence: 99%